Tackling the challenges of visualising digital cadastral plans: The Victorian cadastre experience. (April 2019) - Olfat, Hamed; Jani, Amul; Shojaei, Davood; Darvill, Ashley; Briffa, Mark; Rajabifard, Abbas; Badiee, Farshad
Highlights: The Australian digital cadastre initiative, namely ePlan, has been introduced and discussed. The main challenges of visualising digital cadastral plans in Victoria are discussed and illustrated by images. A research methodology to tackle the digital cadastral data visualisation challenges in Victoria is discussed in detail. Implementation of a tool enabling the surveyors to enhance the presentation of digital cadastral plan is discussed. The results of the usability evaluation of the tool and the future direction for this research are discussed. Abstract: ePlan, as a digital cadastral data initiative, is a collaborative program between the land authorities and the surveying industry which aims to replace paper and PDF cadastral plans and surveys with digital data in LandXML format. ePlan has been adopted by Australia, New Zealand and Singapore. ePlan has been operational in the State of Victoria for 2D plans since 2013. The ePlan files are automatically converted into PDF plans by the ePlan visualisation service within the Victorian state's digital lodgement portal, namely Surveying and Planning through Electronic Applications and Referral (SPEAR). Cadastral plan in PDF format forms part of the legal title in Victoria. Presently, ePlan, in terms of development, has limitations in visualising detailed, complex and large scaled 2D plans. The visualised plan from the LandXML file must comply with accepted Victorian survey drawing standards as the plan is a source for plan certification by council, forms part of a contract of sale, and when the plan is registered by the State of Victoria land authority, Land Use Victoria (LUV), it becomes the title diagram. In addition, through significant engagement with the Victorian Surveying industry, LUV has received feedback from surveyors that they would like to have the ability to enhance the presentation of visualised plans to create enlargements, define additional sheets, exaggerate the position of lines, and move the placement of visualised labels. These enhancement provisions would provide greater scope to ensuring plans complied with the aforementioned drawing standards. A Licensed Surveyor, the creator of the LandXML file is also duty bound to sign the visualised plan. In addressing the abovementioned problem, a research methodology, including the conceptual, choice of technology, development and evaluation phases has been defined and implemented at LUV. The 'conceptual' phase considered the business and technical requirements for developing a tool to support surveyors to enhance the presentation of the visualised ePlans. The 'choice of technology' phase focused on defining the most suitable technologies for developing the tool. In the 'development' phase, the tool was implemented within SPEAR. The surveyors' feedback on the tool usability was collected as part of the 'evaluation' phase. The main outcome of this research has been the ePlan Visualisation Enhancement Tool (VET) developed within SPEAR based on OpenLayers technology, which enables surveyors to improve the presentation of auto-generated cadastral plans. The evaluation phase showed that end users were generally satisfied by the usability of VET and identified the areas that need further improvement. This paper first provides an overview of the ePlan project in Victoria with a focus on the research problem and objective. The relevant interstate and international experiences are then reviewed. Next, the paper discusses the research methodology including the above four phases in detail. The outcomes of the evaluation phase are then discussed. The paper concludes with some discussions around the approach taken for this research, the surveyors' feedback and the future directions.